Diagnostic accuracy of calculated tumor volumes and apparent diffusion coefficient values in predicting endometrial cancer grade - Kakkar, Chandan; Gupta, Kamini; Jain, Kunal; Narang, Vikram; Singh, Aminder; Saggar, Kavita; Bansal, Namita; Cioni, Dania; Neri, Emanuele (International journal of applied and basic medical research, 2022)
Background: Magnetic resonance imaging (MRI) has been shown to be an accurate imaging technique for the preoperative assessment of local staging of endometrial cancer and for evaluating the depth of myometrial invasion. Materials and Methods: This was a single-center retrospective study performed on patients with histopathologically proven endometrial carcinoma who underwent an MRI examination of the pelvis between October 2017 and May 2020. Results: In the present analysis, mean apparent diffusion coefficient (ADC) values for each histologic grade were 0.72 ± 0.13 × 10−3 mm2/s (G1), 0.76 ± 0.17 × 10−3 mm2/s (G2), and 0.74 ± 0.12 × 10−3 mm2/s (G3), respectively, showing no significant correlation between ADC values and tumor grade (P = 0.73). Overall, ADC minimum was significant in differentiating grades of endometrial carcinoma (P = 0.02) with the ability to differentiate Grade I and II lesions (P = 0.01). A mean tumor volume of 25.2 cc could differentiate low-grade tumors (Grade I and Grade II) from high-grade tumors (Grade III) with a sensitivity and specificity of 88% and specificity of 89%. The tumor volume/uterine volume ratio (TV/UV) differentiates high-grade tumors from low-grade tumors (P < 0.001), however, no significant difference in the ratio was observed among Grade I and II lesions (P = 0.48). The area under the curve of tumor volume was 0.875 (95% confidence interval 0.0-1.00) (P = 0.001), indicating that tumor volume was an effective tool for distinguishing high-grade and low-grade endometrioid adenocarcinomas. The corresponding sensitivity and specificity were 88.0% and 89.0%, respectively. Conclusion: Preoperative noninvasive radiological assessment for tumor volume, TV/ UV or tumor volume/uterine volume is important surrogate markers for preoperative prognostication of endometrial carcinoma.